Acute mood and cardiovascular responses to moderate intensity vinyasa yoga, static yin yoga and aerobic exercise in people with depression and/or anxiety disorders: A 5-arm randomised controlled trial. (March 2022) - Brinsley, Jacinta; Smout, Matthew; Girard, Danielle; Davison, Kade
Abstract: Introduction: Due to the multi-composite, mind-body features of yoga, it is of interest to determine what effect exercise plays as a component of modern yoga in providing psychological and physiological health benefits, and whether benefits are enhanced with a combination of components. Furthermore, although the effects of regular, long-term yoga practice are well documented, the acute effects have received less empirical investigation. Method: A within-subjects, repeated measures randomised controlled crossover trial with five conditions was conducted (trial registration: ACTRN12620000983909). Participants (N = 41, mean age = 32 years) with Depressive and/or Anxiety Disorders completed 1) yin yoga, 2) aerobic exercise, 3) vinyasa yoga, 4) stretching (sham) control and 5) no-intervention control. Acute changes in mood and cardiovascular tone were assessed. Results: A significant main effect of condition on mood was observed (N = 38; F 4, 127.193  = 7.507, p = <.001). Participants receiving yin, vinyasa, aerobic exercise and stretching achieved comparable improvements in mood symptoms compared to no-intervention control. Cardiovascular changes were observed for aerobic exercise and vinyasa yoga. No adverse events were reported. Conclusions: The acute mood benefits of a single initial session of yoga are not significantly greater than those derived from other forms of movement. Moderate-intensity styles of yoga can provide a sufficient and equivalent acute cardiovascular exercise effect to that of traditional exercise options (i.e., cycling). Highlights: First study investigating the effects of exercise as a component of yoga on mood in people with depression and/or anxiety. All forms of physical activity, regardless of modality and exercise dose, equally improved mood state. Moderate-intensity yoga can provide a comparable acute cardiovascular exercise effect to that of cycling.